2018
DOI: 10.1111/inm.12484
|View full text |Cite
|
Sign up to set email alerts
|

Promoting exercise behaviour in a secure mental health setting: Healthcare assistant perspectives

Abstract: Individuals with severe mental illness engage in significantly less amounts of physical activity than the general population. A secure mental health setting can exacerbate barriers to exercise, and facilitate physical inactivity and sedentary behaviour. Healthcare assistants are intimately involved in the daily lives of patients and, therefore, should be considered integral to exercise promotion in secure mental health settings. Our aim was to explore healthcare assistants' perceptions of exercise and their at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 24 publications
2
53
0
1
Order By: Relevance
“…Appendix B provides legends for all the tables in the paper. Twelve (12) of the 34 studies in this review, explored the perceptions of HCPs practising in Europe [53,[63][64][65][66][67][68][69][70][71][72][73], 10 were conducted in Australia and New Zealand [31,51,69,[74][75][76][77][78][79][80], five each from the UK [52,[81][82][83][84] and USA [85][86][87][88][89], two from Africa [75,90], and one from India [91]. The study designs were varied with 20 of the 34 included studies employing a cross sectional design [31,[65][66][67][68][70][71][72][73][74]76,79,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Appendix B provides legends for all the tables in the paper. Twelve (12) of the 34 studies in this review, explored the perceptions of HCPs practising in Europe [53,[63][64][65][66][67][68][69][70][71][72][73], 10 were conducted in Australia and New Zealand [31,51,69,[74][75][76][77][78][79][80], five each from the UK [52,[81][82][83][84] and USA [85][86][87][88][89], two from Africa [75,90], and one from India [91]. The study designs were varied with 20 of the 34 included studies employing a cross sectional design [31,[65][66][67][68][70][71][72][73][74]76,79,…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The study designs were varied with 20 of the 34 included studies employing a cross sectional design [31,[65][66][67][68][70][71][72][73][74]76,79,[85][86][87][88][89][90][91][92], the majority of which sampled the opinions of HCPs about PA promotion using questionnaires, 11 studies were qualitative (using semi-structured interviews and focus groups) [52,53,64,69,77,78,[80][81][82][83][84] while longitudinal [51], mixed [75], and multi method [63] designs were employed in one study each. Across the 34 included studies, 20 explored the perceptions of a homogenous group of HCPs [51,64,[67][68][69][70]72,[74][75][76][77][78][79]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that a ward environment conducive of exercise motivated staff would be useful to combat the obesogenic environment on a consistent basis ). Healthcare assistants (HCA's) who are intimately involved in patients' lives due to being on ward 24 hours a day (Cavendish, 2013) are well placed to support people with SMI in exercise participation due to having already established therapeutic relationships (Kinnafick et al, 2018;McAndrew et al 2013).…”
Section: The Impact Of Staff On Patient Physical Activitymentioning
confidence: 99%
“…Studies have shown that formal training for ward staff in exercise and mental health is limited (Stanton, Happell & Reaburn, 2015). Whilst members of staff recognise the benefits of exercise in SMI (Kinnafick et al, 2018;Robson, Haddad, Gray & Cournay, 2012), confidence to deliver exercise sessions is low (Verhaeghe, De Measeneer, Maes, Van Heeringen & Annemans, 2011). It has been suggested that it would be useful to incorporate exercise training for psychiatric staff into professional development sessions (Stanton et al, 2015) and focus on behaviour change in SMI to target barriers unique to mental health consumers (Arbour- Duncan, Remington, Cairney & Faulkner, 2014).…”
Section: The Impact Of Staff On Patient Physical Activitymentioning
confidence: 99%